Spatial Distribution Of Heavy Metals Cd And Cu In Water, Sediment And Fish (Mugil Sp) In Pelawangan East Segara Anakan Cilacap: Spatial Distribution Of Heavy Metals Cd And Cu In Water, Sediment And Fish - Prayogo, Norman Arie; Hidayati, Nuning Vita; Siregar, Asrul Sahri; Sukardi, Purnama; Fitriadi, Ren (Department of Aquaculture, 2024)
Heavy metals are widely known pollutants with bioaccumulative nature, so they can be transferred and accumulated in biota, such as mullet fish (Planiliza subviridis). The heavy metals Cd and Cu have different anthropogenic and natural sources. Heavy metals have the potential to absorb existing biota such mullet fish. Fish absorb metals from the water in the body through gills, skin surface and food. This study aims to identify Cd and Cu metals in distribute water, sediment and mullet fish in the Plawangan Timur, Segara Anakan lagoon, Cilacap, Central Java, and the relationship between aquatic media and sediment and mullet fish. The study used a research method with a targeted random sampling method at five stations with four replications. The survey was conducted from April to September 2020. Descriptive data analysis, F-test, regression and correlation. The results showed in water, sediment and mullet fish the heavy metal content of Cd and Cu varied between stations. The correlation between the Cd and Cu metals in water, sediment and mullet fish showed a positive correlation. The content of heavy metal Cd in mullet fish media in Plawangan Timur Segara Anakan Cilacap has exceeded the specified quality standard, while for heavy metal Cu in mullet fish is still below the specified quality standard.